The new trend? The use of the 'double nomination' electoral rule in Costa Rican Elections (1998-2022) - Aguirre Raftacco, Eugenia C. (2023)
The article analyzes and describes the research findings of the use of the 'double nomination' electoral rule in Costa Rica’s national elections, from 1998 to 2022. The aim is to answer the research question: how has this rule been used? The electoral rule named 'double nomination' consists of the possibility that in the same election a candidate may run for the presidential or vice presidential candidacy with a double nomination for deputy also, in the same electoral process.  In Costa Rica, double nomination dates back to 1996 and has been used in all elections. However, in 2022 the number of candidates using double nomination increased. In regard to this, the study analyzes and describes the trends in the use of this rule. We created an original database that describes the universe of cases in which the rule has been applied. In turn, semi-structured interviews were conducted with presidential candidates who use the double nomination rule in the 2022 national election and previous ones, in order to explore key factors influencing the use of the double nomination rule in Costa Rica. Finally, the study presents preliminary conclusions.